If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 1(4x + -2) = 2x + -1(3x + -1) Reorder the terms: X + 1(-2 + 4x) = 2x + -1(3x + -1) X + (-2 * 1 + 4x * 1) = 2x + -1(3x + -1) X + (-2 + 4x) = 2x + -1(3x + -1) Reorder the terms: -2 + X + 4x = 2x + -1(3x + -1) Reorder the terms: -2 + X + 4x = 2x + -1(-1 + 3x) -2 + X + 4x = 2x + (-1 * -1 + 3x * -1) -2 + X + 4x = 2x + (1 + -3x) Reorder the terms: -2 + X + 4x = 1 + 2x + -3x Combine like terms: 2x + -3x = -1x -2 + X + 4x = 1 + -1x Solving -2 + X + 4x = 1 + -1x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '2' to each side of the equation. -2 + X + 2 + 4x = 1 + 2 + -1x Reorder the terms: -2 + 2 + X + 4x = 1 + 2 + -1x Combine like terms: -2 + 2 = 0 0 + X + 4x = 1 + 2 + -1x X + 4x = 1 + 2 + -1x Combine like terms: 1 + 2 = 3 X + 4x = 3 + -1x Add '-4x' to each side of the equation. X + 4x + -4x = 3 + -1x + -4x Combine like terms: 4x + -4x = 0 X + 0 = 3 + -1x + -4x X = 3 + -1x + -4x Combine like terms: -1x + -4x = -5x X = 3 + -5x Simplifying X = 3 + -5x
| 20-3z=7z+8 | | x/10+6=8 | | 2(2x+3)-3=5 | | 4(2x-1)+4=x+25 | | 3.3z-2.3z+0.4=-7.2 | | (4-2i)(6-5i)=0 | | -33=3(4c+5) | | (x+5)2=16x | | x+2(49)=115 | | (5y+2)(3y-1)= | | 3(2x-1)+4=y+25 | | x(x)=1525 | | (x^2)+(18x)+(90)=0 | | 2.5(x-3.6)=x(1.6) | | n+10=3n-10 | | F=3.14msquaredx | | Y=5E+07x+3E+08 | | -(7x-2y-3)= | | 6x=277+3x | | F=3.14msguaredx | | 2(3x-3)=-9 | | (2n-4)-(4n-3)=a | | 5x^2=128 | | 3x^2=15x+42 | | 6.8y-5.8y-9.1=8.4+9.5 | | (-3i)(7i)(-i)=0 | | -1=5x+4 | | X^2-7x+12.5=0 | | 21=3s-4(21-s) | | 8m^2=-16m+384 | | X(1.6)=2.5(x-3.6) | | 4+92=15 |